Tissue nitric oxide synthase activity in the oral cavity in atopic disease. - Nazarian, R. S.; Krivenko, L. S.; Gargin, V. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Today there is a necessity for significant clinical and experimental studies considering the pathogenesis of atopic diseases development in view of their increasing frequency, including children. Objective. The aim of this study was to identify the activity of endothelial and inducible nitric oxide synthase (eNOs and iNOs) in soft tissues of the oral cavity of experimental animals in the simulation of atopic disease. Methods. Experimental study was performed with sensitization of animals by ovalbumin for modeling the atopic process. Histological and immunohistochemical studies were performed for detection the activity of eNOs and iNOs in soft tissue of oral cavity. Results. There is a pronounced uneven thickness of squamous layer with the presence of intraepithelial lymphocytes, eosinophils, focal erosion, areas of necrosis, proliferation of basal layer of the epithelium of oral cavity in animals with atopy. Formation of perivascular inflammatory infiltrates, diffuse distribution of eosinophils, swelling of connective tissue fibers are observed in the lamina propria. eNOs immunoreactivity is detected in altered and unaltered areas in the mucous membrane of the oral cavity with appearance of extravascular localization in atopic animals. Morphometric studies revealed that the level of activity of eNOs is not significantly different for vascular wall in different groups of animals, while extravascular localization of eNOs significantly higher in the group of experimental animals. The results of the iNOs detection in the group of animals with experimental atopy showed more pronounced intensity. There are areas with a diffuse and focal increase of immunopositive staining tissue. The presence of such zones can be attributed to the interaction of the immunomodulatory fraction of nitric oxide synthase and inflammatory cells. The most pronounced activity of iNOs is detected in the affected areas and associated with focal perivascular inflammatory infiltration and intensity of immunoreactivity associated with the quantitative and qualitative composition of the cell infiltration in tissues with atopy. Conclusion. It was established that in atopic processes in the oral cavity morphological picture is characterized by inflammatory, degenerative, dyscirculatory changes which are accompanied by disturbance of nitric oxide synthase metabolism. It is characterized by more than doubled increase in activity of inducible nitric oxide synthase and increased activity of endothelial nitric oxide synthase in the extravascular space.